Case Report : Fahr’s Disease With Acute Double Hemiparese Manifestation - Vania Ayu Puspamaniar; Giam, Billy Putera Kurniawan; Bonfilio Neltio Ariobimo; Lisa Puspitorini (Jurnal Kedokteran Diponegoro (Diponegoro Medical Journal), 2023)
Fahr's disease is a very rare disease with a prevalence of 1/1,000,000 individuals. We present a case report of a male with sudden double hemiparese and basal ganglia calcification leading to the diagnosis of Fahr's disease. A 59 years old male presented to the emergency department with a chief complaint of unable to move his upper and lower extremities in a sudden. The complaint begins with weakness of the right side of the body, followed by weakness of the left side of the body the day after. The serum levels of calcium, magnesium, phosphorus, and Parathyroid Hormonal (PTH) have not been measured due to the patient’s financial problems. CT scan of the brain showed bilateral, symmetrical, wide areas of calcification over the fossa posterior, basal ganglia, periventricular, and parietal area, which were suggested as Fahr’s disease. The patient is being treated with the injection of neuroprotectant, antibiotic, vitamin, neuropathic analgesia, and fluids. He is also being consulted with medical rehabilitation to get some physical treatments. Treatment goals include: increase and or maintain ROM, prevent contractures, strengthens weak muscles that may be underutilized, improvement and maintenance of postural stability in static postures and during mobility, and fall prevention. Our case highlight sudden double hemiparese which different from previous literature which says that neurological deficit symptoms appear with a chronic nature and the importance of combining pharmacological therapy and physical therapy as in this patient to reduce the patient's morbidity.